2019
DOI: 10.1590/1678-9199-jvatitd-1481-18
|View full text |Cite
|
Sign up to set email alerts
|

Scorpion toxins targeting Kv1.3 channels: insights into immunosuppression

Abstract: Scorpion venoms are natural sources of molecules that have, in addition to their toxic function, potential therapeutic applications. In this source the neurotoxins can be found especially those that act on potassium channels. Potassium channels are responsible for maintaining the membrane potential in the excitable cells, especially the voltage-dependent potassium channels (Kv), including Kv1.3 channels. These channels (Kv1.3) are expressed by various types of tissues and cells, being part of several physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 161 publications
2
20
0
Order By: Relevance
“…Cytokines play a key role in amplifying the response/communication among cell types, building an efficient response against pathogens. Herein, TsV, F6, and F7 fractions were potent inducers of IL-12p70/TNF/IL-6 in MOs, which is consistent with previous studies demonstrating that TsV-stimulated MOs secrete IL-1/IL-6/TNF/IFN-γ ( Petricevich, 2002 ; Oliveira et al., 2019 ; Pimentel et al., 2021 ). Of great relevance, we demonstrated that TsV compounds induced the production of IL-12 and TNF by T. gondii -infected MOs, abolishing the capacity of the parasite to evade host immunity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Cytokines play a key role in amplifying the response/communication among cell types, building an efficient response against pathogens. Herein, TsV, F6, and F7 fractions were potent inducers of IL-12p70/TNF/IL-6 in MOs, which is consistent with previous studies demonstrating that TsV-stimulated MOs secrete IL-1/IL-6/TNF/IFN-γ ( Petricevich, 2002 ; Oliveira et al., 2019 ; Pimentel et al., 2021 ). Of great relevance, we demonstrated that TsV compounds induced the production of IL-12 and TNF by T. gondii -infected MOs, abolishing the capacity of the parasite to evade host immunity.…”
Section: Discussionsupporting
confidence: 92%
“…T. serrulatus Venom Against Toxoplasma consistent with previous studies demonstrating that TsVstimulated MOs secrete IL-1/IL-6/TNF/IFN-g (Petricevich, 2002;Oliveira et al, 2019;Pimentel et al, 2021). Of great relevance, we demonstrated that TsV compounds induced the production of IL-12 and TNF by T. gondii-infected MOs, abolishing the capacity of the parasite to evade host immunity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In particular, those inhibiting K v 1.3 currents are considered potential bioactive molecules to treat autoimmune diseases (Zhao et al, 2015). To the best of our knowledge, there are 81 scorpion toxins with positive results in inhibiting K v 1.3 (Oliveira et al, 2019). Nevertheless, only eight of them present in vivo assays (i.e.…”
Section: Scorpionsmentioning
confidence: 99%
“…Many peptides that act on K V 1.3 with excellent potencies have been isolated and described 6,127 . A frequently occurring pitfall, however, is insufficient selectivity for K V 1.3 over other K V channels, and especially over K V 1.1, because of its high homology to K V 1.3 (65%–70%) 73 .…”
Section: Discovery and Development Of Peptide‐based Kv13 Inhibitorsmentioning
confidence: 99%